HIV-1 transmission patterns in men who have sex with men: insights from genetic source attribution analysis. - Le Vu, S; Ratmann, O; Delpech, V; Brown, A; Gill, O; Tostevin, A; Dunn, D; Fraser, C; Volz, E (Mary Ann Liebert, 2019)
BACKGROUND:Near 60% of new HIV infections in the United Kingdom are estimated to occur in men who have sex with men (MSM). Age-disassortative partnerships in MSM have been suggested to spread the HIV epidemics in many Western developed countries and to contribute to ethnic disparities in infection rates. Understanding these mixing patterns in transmission can help to determine which groups are at a greater risk and guide public health interventions. METHODS:We analyzed combined epidemiologic data and viral sequences from MSM diagnosed with HIV at the national level. We applied a phylodynamic source attribution model to infer patterns of transmission between groups of patients. RESULTS:From pair probabilities of transmission between 14 603 MSM patients, we found that potential transmitters of HIV subtype B were on average 8 months older than recipients. We also found a moderate overall assortativity of transmission by ethnic group and a stronger assortativity by region. CONCLUSIONS:Our findings suggest that there is only a modest net flow of transmissions from older to young MSM in subtype B epidemics and that young MSM, both for Black or White groups, are more likely to be infected by one another than expected in a sexual network with random mixing.